Content of stem tumor CD133⁺ cells in brain neoplasms of different histological type - Lisyaniy, N.I.; Stanetskaya, D.N.; Lisyaniy, A.N.; Belskaya, L.N. (Experimental Oncology, 2017)
Today, there are conflicting data on the content of cancer stem cells responsible for recurrence and resistance to chemotherapy in tumors of human brain. The aim of the study was to analyze the content of CD133⁺cells in different brain tumors by immunofluorescence assay and immunohistochemical method. Materials and Methods: The samples of different brain tumors removed during neurosurgical operations were studied for CD133 expression. Results: Immunofluorescence assay of tumor imprints revealed CD133⁺cells in 40–85% of tumors regardless of histological type. In malignant tumors, the count of CD133⁺cells was higher than in benign tumors. Immunohistochemical method used for detection of CD133⁺cells was less sensitive than immunofluorescence technique. The number of CD133⁺cells may vary even in tumors of the same histological type. In 20–30% of malignant tumors (glioblastomas, medulloblastomas), the content of CD133⁺cells was very low or not detected at all. Conclusions: In tumors of the brain of different genesis and degree of anaplasia CD133⁺cells are found out. In malignant tumors (glioblastomas and medulloblastomas), CD133⁺cells are much more frequently detected than in benign brain tumors. The content of CD133⁺cells in brain tumors is highly variable being small and some malignant tumors, indicating low predictive and diagnostic value of cancer stem cell content in clinical practice.